The Law Responsibility of E-Commerce Organizers Regarding The Failure of Payment in PayLater System - Mutiarawati, Intan; Dewantara, Reka; Rachmat, Sigit Nur (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
In today’s era, technology is increasingly developing with various provided conveniences. The disruption era presents the power of technology, information, and communication using the benefits of internet media. One of them is the needs of society and the development of payment methods which continue to evolve. PayLater makes the easier solution to meet your needs. However, with the many conveniences and the increasing number of users, there are also problems regarding the failure of payment which reached the Non-Performing Loan (NPL) ratio DPD30+ as of April 2023 in the amount of 9.7% or above the safe limit of the NPL ratio which is in the percentage of 5%. Deriving from that, protection for financial technology is needed when there are many failures of payment from PayLater payment system through e-commerce employing the preventive legal protection, risk management, and the principle of prudence by PayLater organizers, as well as the repressive legal protection using the expected compensation method.